Features of intertidal bioerosion and bioconstruction on Limestone Coasts of Langkawi Islands, Malaysia - Kazmer, Miklos; Mohd Shafeea Leman; Kamal Roslan Mohamed; Che Aziz Ali; Taborosi, Danko (Universiti Kebangsaan Malaysia, 2015)
The purpose of this paper was to provide a practical guide assisting field workers in identification and interpretation of frequently occurring bioerosional textures created in limestone by intertidal organisms along the coasts of Langkawi Islands, Malaysia. The discussion follows the textural succession from the supratidal down to the lower intertidal zone. Traces left by lichens, boring sponges, molluscs (littorinid snails, the chiton Acanthopleura, the bivalve Lithophaga) and the echinoid Echinometra are illustrated. Products of bioconstructing organisms, specifically oysters and barnacle are also described. Ecological tolerance of each group is given.